A Munkácsi Görögkatolikus Egyházmegye főpapsága és a ruszin identitás viszonyrendszere 1848–1849-ben - Molnár Ferenc; Молнар Федір; Molnar Fedir (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"TIMPANI", 2014)
A vallás nagy hatással volt a kelet-európai nemzetek fejlődésére. Ez különösen igaz a ruszinokra, akik inkább azonosították magukat vallási hovatartozásuk, mint nemzetiségük szerint. A Magyar Királyságban élő ruszinok többsége a Munkácsi Görögkatolikus Egyházmegye joghatósága alá tartozott. Munkánkban a ruszin elit nemzeti identitásról vallott nézeteit kíséreljük meg bemutatni. Kutatásunkat a ruszin görögkatolikus papság 1848–1849-es helyzetét bemutató esettanulmányok segítségével végeztük el. Vizsgálódásunkat Miroslav Hroch nacionalizmusok fejlődését illetően kidolgozott ún. háromlépcsős koncepciójára alapoztuk.

Резюме. Релігія завжди відігравала велику роль у розвітку народів Східної Європи. Це особливо вірно для русинів, які більш ідентифікували себе з релігійною приналежністю, ніж з національністю. Русини, які проживали в Угорській королівстві переважно належали до юрисдикції Мукачівської греко-католицької єпархії. У статті пробуємо представляти погляди русинської еліти про національну ідентичність. Дослідження проведені за допомогою наукових статей про становище русинського греко-католицького духовенства у 1848–1849 рр. Дослідження була заснована на триступеневу концепцію Мирослава Гроха про розвиток націоналізм.

Abstract. Religion has always exerted a deep impact on national development in Eastern Europe. This holds true in case of the Rusyns, who identified themselves rather by religious affiliation than by nationality. In the Hungarian Kingdom, most of them lived under the jurisdiction of the Greek Catholic Eparchy of Mukachevo (Munkács). In our work we tried to define the basic beliefs of the Rusyn elite (Greek Catholic clergy) about national identity. Our research was carried out by means of case studies closely associated with the position of the Rusyn Greek Catholic clergy in 1848–1849. Our examination was based on Miroslav Hroch’s concept of the three-stage process of nationalist mobilization.
Ставлення керівництва Мукачівськoї греко-католицькoї єпархії до русинcькoї ідентичності у 1848–1849 pp.
The Relation Between the Hierarchs of the Greek Catholic Eparchy of Mukachevo and Rusyn Identity in 1848–1849
https://www.kmf.uz.ua/hun114/letoltes/acta/Acta_Ac_Bereg_2014_1.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/160302
Keywords: Munkácsi Görögkatolikus Egyházmegye; ruszin identitás; főpapság; 1848–1849